Proceeding of the 9th Asia-Pacific chitin and chitosan symposium : (Agricultural Publishing House, 2012)
Synthesis and characterisation of metal-free thiocarbamoyl chitosan gel, antioxidant and antibacterial chitosan film based on polydopamine modification,...